The Relationship Between Quality of Service and Satisfaction of Sosial Health InsuranceCustomersat Public Health Centre - Shanti Probosiwi; Hartanto; Endang Sutisna Sulaeman (Nexus Kedokteran Komunitas, 2017)
Background: Since January 2015, government has enacted the National Health Insurance System (SJKN) held by Badan Penyelenggara Jaminan Sosial (BPJS) to achive universal health coverage. Puskesmas as primary public health service has an important role to improve customer satisfaction by providing the best quality of health services. Customer satisfaction is one of the main indicators to measure the quality of health service. This research aims to analyze the relationship between the of service and satisfaction of Social Health Insurance Customers at public health care in term of five quality service dimension (tangible, responsiveness, assurance, reliability and empathy) . Methods:This research was a observational analitic study with cross-sectional design, conducted at Puskesmas Kebakkramat I Karanganyar District. Sampling technique used in this research is random sampling technique. The samples were customers of BPJS in Puskesmas Kebakkramat I Karanganyar District that meet the inclusion and exclusion criteria of at least 93 respondents. In this research, respondents filled out some questionnaire of patient satisfaction and quality of health service, and then the data were analyzed with Kendall's tau_b correlation test. Results:The result of Kendall's tau_b correlation test showed a significant relationship between health service quality and satisfaction of BPJS customers at PuskesmasKebakkramat I Karanganyar District with p ?0.000. Conclusions:From this research, researcher conclude that there is a relation between health service quality and satisfaction of BPJS customer at Puskesmas Kebakkramat IKaranganyar District. Keywords: Health service quality, customer satisfaction, BPJS